Influence of interpersonal discussion on contraceptive use a study of the Philippine case - David, Clarissa C.; Atun, Jenna Mae L. (2009)
Interpersonal influence through communication is a complex process that bears important implications on attitudes, preferences, and behaviors. This study examines the role of interpersonal communication about family planning (FP) and sexuality on decisions to use contraceptives. Secondary analysis of data from nationally-representative sample surveys shows that among women non-users, discussions of FP with partner and relatives significantly predict intention to use contraceptives. However, for both men and women users, only discussing with partner about FP significantly predicts preference for modern contraceptive methods over non-modern ones. Although very few young men and women discuss sex at home, bivariate analyses show that among the married sample, discussing sex with others has a significant relationship with contraceptive use. Implications and recommendations for family planning campaigns and intervention programs are discussed.